Brain Arousal as Measured by EEG-Assessment Differs Between Children and Adolescents With Attention-Deficit/Hyperactivity Disorder (ADHD) and Depression - Berger, Christoph; Dück, Alexander; Perin, Felicitas; Wunsch, Katharina; Buchmann, Johannes; Kölch, Michael; Reis, Olaf; Marx, Ivo (Frontiers in Psychiatry, 2021)
Objective: Disturbed regulation of vigilance in wake state seems to play a key role in the development of mental disorders. Hegerl et al. (2014) introduced a model of dysfunctional arousal regulation for affective disorders and for ADHD. They assume that hyperactivity in adult ADHD is an attempt to increase a general low vigilance level via external stimulation in order to avoid drowsiness. For depression the avoidance of stimulation is interpreted as a reaction to a tonic increased vigilance state. Although ADHD is assumed to start during childhood, this vigilance model has been barely tested with children diagnosed for ADHD so far. Methods: Resting state EEG (8 min) measures from two groups of children diagnosed with either ADHD (N=76 (16 female, 60 male) , age: (mean/sd) 118/33 month) or depression(N=94 (73 female, 21 male), age: 184/23 month) were analyzed. Using the VIGALL toolbox EEG-patterns of vigilance level and regulation were derived and compared between both groups. In correlation analysis, the relations between vigilance measures, attentional test performance (alertness and inhibition) and mental health symptoms were analyzed. Results: Children with ADHD differed from children with most prominent depressive symptoms in brain arousal regulation and level, but EEG vigilance was not related to behavior problems and not related to the attentional test performance. Brain arousal was dependent on the age of the participant in the whole sample; younger children showed lower vigilance stages than teenagers, this effect was not present when analyzed separately for each diagnostic group. EEG assessment time and received medication had no effect on the EEG vigilance. Discussion: Although based on a small sample, this explorative research revealed that EEG vigilance level is different between children with ADHD and with depression. Moreover, even the standard procedure of the clinical routine EEG (resting state), can be used to differentiate brain arousal states between participants with ADHD and depression. Because routine EEG is not specialized to vigilance assessment, it may not be sufficiently sensitive to find vigilance-symptomatology associations. Further research should address developmental changes in EEG measurements in children and use bigger samples of participants within the same age range.